Effect of Nurse Therapeutic Communication on Patient Satisfaction - Mahyana Mahyana; Efridariani Sari Gulo; Erwasan Laia; Reli Sugianto; Sunarti Sunarti (LPPM STIKES KENDAL, 2020)
Therapeutic communication is important for nurses in nursing care. Good communication can foster trust between nurses and patients and can increase patient satisfaction and quality of care. The purpose of this study was to determine the effect of therapeutic communication on patient satisfaction. Correlation research with cross-sectional design. The sample consisted of 65 patients. Therapeutic communication questionnaire instrument and patient satisfaction with the validity 0,80 and 0,87 dand reliability test with cronbachapha 0,79 and 0,86. Data analysis using Pearson correlation. The results were obtained for the effect of therapeutic communication on patient satisfaction p = 0.00 (p <0.05).